Developing an Instrument to Assess Chemical Literacy for Prospective Chemistry Teachers - Ardyansyah, Ananta; Rahayu*, Sri; Munzil, Munzil; Yahmin, Yahmin; Alsulami, Naif Mastoor (Universitas Syiah Kuala, 2025)
The lack of instruments designed to assess chemical literacy among prospective chemistry teachers highlights the need for robust tools to support science education. This study develops and validates an instrument to measure chemical literacy, addressing this gap and contributing to improved pedagogical practices. In this study, a chemical literacy instrument for general chemistry was developed, drawing on existing frameworks of chemical literacy. This research employs a development-based approach (RD), encompassing literature review, instrument development, and quality testing. The quality of the instrument was evaluated based on its reliability and validity. The validity was evaluated by expert panel review, difficulty index, discrimination index, and pearson correlation value. In this study, a multiple-choice chemical literacy test instrument was successfully developed using the PISA 2025 scientific literacy framework, resulting in 23 valid items. The PISA framework was chosen for its perceived dynamism compared to other frameworks. The reliability of the developed instrument reached 0.818, indicating that the questions are highly reliable. Future improvements to the instrument are necessary, with a focus on ensuring that all items fully meet the established validity criteria